Exogenous 6-BA inhibited hypocotyl elongation under darkness in Picea crassifolia Kom revealed by transcriptome profiling - Liu, Hongmei; Zhou, Chengcheng; Nisa, Zaib Un; El-Kassaby, Yousry A.; Li, Wei (Frontiers in Plant Science, 2023)
Hypocotyl elongation is an important process in plant growth and development, and is under hormonal regulatory signaling pathways. In our study, exogenous 6-BA significantly inhibited Picea crassifolia hypocotyl elongation more than ethylene in the dark, indicating the existence of different regulatory strategies in conifers, therefore, the P. crassifolia transcriptome was studied to explore the responsive genes and their regulatory pathways for exogenous N6-benzyladenine (6-BA) inhibition of hypocotyl elongation using RNA-Sequencing approach. We present the first transcriptome assembly of P. crassifolia obtained from 24.38 Gb clean data. With lowly-expressed and short contigs excluded, the assembly contains roughly 130,612 unigenes with an N50 length of 1,278 bp. Differential expression analysis found 3,629 differentially expressed genes (DEGs) and found that the differential expression fold of genes was mainly concentrated between 2 and 8 (1 ≤ log2FoldChange ≤ 3). Functional annotation showed that the GO term with the highest number of enriched genes (83 unigenes) was the shoot system development (GO: 0048367) and the KEGG category, plant hormone signal transduction (ko04075), was enriched 30 unigenes. Further analysis revealed that several cytokinin dehydrogenase genes (PcCTD1, PcCTD3 and PcCTD6) catabolized cytokinins, while xyloglucan endotransglucosylase hydrolase gene (PcXTH31), WALLS ARE THIN 1-like gene (PcWAT1-1) and Small auxin-induced gene (PcSAUR15) were strongly repressed thus synergistically completing the inhibition of hypocotyl elongation in P. crassifolia. Besides, PcbHLH149, PcMYB44 and PcERF14 were predicted to be potential core TFs that may form a multi-layered regulatory network with the above proteins for the regulation of hypocotyl growth.